DEVELOPMENT OF INTEGRATED SCIENCE TEACHING MATERIALS MODEL PROBLEM BASED LEARNING (PBL) LOCAL WISDOM CLASS VII SMP - Melani Norma Wijaya; Yurnetti Yurnetti (Universe, 2023)
The COVID-19 pandemic, the implementation of learning for the yellow, orange, and red zone areas is prohibited from face-to-face learning while the green zone area is allowed. Demanding teachers to make teaching materials that help students learn at home and at school. This study aims to produce teaching materials for Integrated Science Problem Based Learning models based on valid and practical local wisdom. This type of research using the Plomp model consists of three stages, namely: the initial investigation stage, the prototype formation stage and the assessment stage. The research subjects were 3 science education lecturers, FMIPA UNP, teachers and students of SMP N 03 Solok Selatan. The instruments used in this study were validation questionnaires and practical questionnaires. The data in this study used the momem kappa formula, the results of the validity test were 0.83 with a very high category, the practical results of students and teachers were obtained 0.84, 0.82 and 0.83 with a very high category. It can be concluded that the integrated science teaching materials using the Problem Based Learning model based on local wisdom are valid and practical to use in class VII SMP